Directing Traffic: Halogen‐Bond‐Mediated Membrane Transport. Issue 48 (8th July 2019) - Govindaraj, Vijayakumar; Ungati, Harinarayana; Jakka, Surendar R.; Bose, Sritama; Mugesh, Govindasamy
Abstract: The plasma membrane regulates the transport of molecules into the cell. Small hydrophobic molecules can diffuse directly across the lipid bilayer. However, larger molecules require specific transporters for their entry into the cell. Regulating the cellular entry of small molecules and proteins is a challenging task. The introduction of halogen, particularly iodine, to small molecules and proteins is emerging to be a promising strategy to improve the cellular uptake. Recent studies reveal that a simple substitution of hydrogen atom with iodine not only increases the cellular uptake, but also regulates the membrane transport. The strong halogen‐bond‐forming ability of iodine atoms plays a crucial role in the transport and the introduction of iodine may provide an efficient strategy for studying membrane activity and cellular functions and improving the delivery of therapeutic agents. This Concept article does not provide a comprehensive picture of membrane transport but highlights halogen‐substitution as a novel strategy for understanding and regulating the cell‐membrane traffic. Abstract : Cellular uptake : The introduction of halogen, particularly iodine, atoms to small molecules and proteins is emerging as a novel and promising strategy not only for studying membrane activity and cellular functions, but also for improving the delivery of therapeutic agents. The strong halogen‐bond forming ability of iodine atoms plays a crucial role in membrane transport (see scheme).